METODE DAN PERTIMBANGAN UNTUK MELEPAS RESTORASI CEKAT SECARA KONSERVATIF - Eri H. Jubhari (DiscoverSys Inc., 2002)
A fixed restoration should be removed because it hasdistortions at the restoration or its abutment. It's not an easyprocess, especially when it has been cemented permanently. Todo so, it is necessary to know the restoration history, cement,abutment,